Molecular analysis of Salmonella enteritidis by pulsed-field gel electrophoresis and ribotyping - Thong, Kwai Lin; Ngeow, Y.F.; Altwegg, M.; Navaratnam, P.; Pang, T. (American Society for Microbiology, 1995)
A total of 61 isolates of Salmonella enteritidis were analyzed by the techniques of pulsed-field gel electrophoresis (PFGE) and ribotyping. Twenty-three of the isolates were from Zurich, Switzerland, and 38 isolates were from the University Hospital, Kuala Lumpur, Malaysia. Five of the Malaysian isolates were hospital-related outbreak strains and were shown to be indistinguishable by PFGE analysis following digestion with three different restriction endonucleases, XbaI (5'-TCTAGA-3'), SpeI (5'-ACTAGT-3'), and AvrII (5'-CCTAGG-3'). The PFGE pattern of an isolate from a suspected carrier staff nurse was found to be identical to those of the hospital outbreak isolates. These isolates were also indistinguishable by ribotyping with SmaI and SphI. The same single PFGE pattern was also detected in 29 of 32 sporadic isolates of S. enteritidis. Four closely related ribotypes were detected among these 29 isolates. Similarly, outbreak-related strains from Switzerland showed close genetic identity by PFGE and ribotyping. Strains obtained from poultry showed more variations in their PFGE patterns and ribotypes, although the patterns were still closely related. In addition, SphI ribotypes A and D among the Swiss strains correlated with phage types 4 and 8, respectively. No correlation of phage types with PFGE pattern was noted. Both PFGE and ribotyping indicate that the S. enteritidis strains circulating in Malaysia and Switzerland are very similar and may be clonally related. Comparison of the PFGE patterns with the ribotypes for 23 Swiss and 16 Malaysian isolates showed that there was a 69% concordance in the grouping of isolates. We conclude that the close genetic similarity observed between epidemiologically unrelated and outbreak-related isolates of S. enteritidis suggests that both PFGE and ribotyping are of limited value in the epidemiological analysis of these particular isolates, possibly because of the highly clonal nature of pathogenic strains of S. enteritidis.